Phenotypic Dimensions of Spirituality: Implications for Mental Health in China, India, and the United States - McClintock, Clayton H.; Lau, Elsa; Miller, Lisa (Frontiers in Psychology, 2016)
While the field of empirical study on religion and spirituality in relation to mental health has rapidly expanded over the past decade, little is known about underlying dimensions of spirituality cross-culturally conceived. We aimed to bridge this gap by inductively deriving potential universal dimensions of spirituality through a large-scale, multi-national data collection, and examining the relationships of these dimensions with common psychiatric conditions. Five-thousand five-hundred and twelve participants from China, India, and the United States completed a two-hour online survey consisting of wide-ranging measures of the lived experience of spirituality, as well as clinical assessments. A series of inductive Exploratory Factor Analysis (EFA) and cross-validating Exploratory Structural Equation Modeling (ESEM) were conducted to derive common underlying dimensions of spirituality. Logistic regression analyses were then conducted with each dimension to predict depression, suicidal ideation, generalized anxiety, and substance-related disorders. Preliminary EFA results were consistently supported by ESEM findings. Analyses of 40 spirituality measures revealed five invariant factors across countries which were interpreted as five dimensions of universal spiritual experience, specifically: love, in the fabric of relationships and as a sacred reality; unifying interconnectedness, as a sense of energetic oneness with other beings in the universe; altruism, as a commitment beyond the self with care and service; contemplative practice, such as meditation, prayer, yoga, or qigong; and religious and spiritual reflection and commitment, as a life well-examined. Love, interconnectedness, and altruism were associated with less risk of psychopathology for all countries. Religious and spiritual reflection and commitment and contemplative practice were associated with less risk in India and the United States but associated with greater risk in China. Education was directly associated with dimensions of spiritual awareness in India and China but inversely associated with dimensions in the United States. Findings support the notion that spirituality is a universal phenomenon with potentially universal dimensions. These aspects of spirituality may each offer protective effects against psychiatric symptoms and disorders and suggest new directions for treatment.